Supercritical-fluid synthesis of FeF2 and CoF2 Li-ion conversion materials - MORRIS, MICHAEL (My University, 2013)
The synthesis of the Li-ion conversion candidates, FeF2 and CoF2, obtained from the single source organometallic precursors [Fe(tta)3] (tta = C8H4F3O2S), and [Co(hfac)2·2H2O] (hfac = C5H1F6O2), respectively, via a novel supercritical fluid (SCF) method is presented. The nature of the synthesis led to highly-crystalline FeF2 and CoF2 powders requiring no additional thermal treatment. The as-obtained powders were investigated for use as potential positive Li-ion conversion electrodes by means of chronopotentiometric measurements. The FeF2 cells displayed high initial capacities following electrochemical conversion (up to [similar]1100 mA h g−1 at a potential of 1.0 V vs. Li/Li+), with appreciable cyclic behaviour over 25 discharge–charge cycles. The deposition of a [similar]5 nm layer of amorphous carbon onto the surface of the active material following SCF treatment, likely facilitated adequate electron transport through an otherwise poorly conducting FeF2 phase. Similarly, CoF2 cells displayed high initial capacities (up to [similar]650 mA h g−1 at a potential of 1.2 V vs. Li/Li+), although significant capacity fading ensued in the subsequent cycles. Ex situ XRD measurements confirmed a poor reversibility in the conversion sequence for CoF2, with a complete loss of CoF2 crystallinity and the sole presence of a crystalline LiF phase following charging.
PUBLISHED
Cited By :2 Export Date: 11 December 2014
Keywords: Chemistry